The effect of cultural organization organizational commitment and work facilities to the employee performance Bank Sumut Medan - Syaukani, Arham; Napitupulu, Dea Okviar Egano (Institute of Computer Science (IOCS), 2024)
Bank Sumut is a BUMD which is well-known for its organizational culture and in recent years Bank Sumut has had a new leader in which the CEO has a background as a leader at Bank Danamon, so this study aims to determine the overall cultural influence between organizational culture, organizational commitment andmjob opportunities on the performance of employees in the central bank office in North Sumatra, in the human resources department and in the retail department. The population in this study consisted of employees from the North Sumatra Medan Bank Office, Human Resources and the Retail Department. The results of the regression analysis showed that of the three independent variables contained in the regression model (organizational culture, organizational commitment and job opportunities). The variables of the organizational culture are significant at 0.04, concluded that the performance of the employees is influenced by the organizational culture (hypothesis 1 is accepted). The variable organizational commitment has a significant value of 0.048. concluded that the organizational commitment influences the performance of the employees (hypothesis 2 is accepted). Workplace variable with a significant value of 0.00. concluded that work facilities influence the performance of employees (hypothesis 3 is accepted). The results showed that the variables organizational culture, organizational commitment and job opportunities together have a positive effect on employee performance. T values with a probability of 0.000 below α (α = 0.05). It can be explained that organizational culture, organizational commitment and work facilities have a positive impact on employee performance.